The impact of recent trends of the Central Bank of Iraq in activating bank credit for the private commercial banking sector (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:                 Central banks seek to control and supervise credit and follow it up effectively due to the high credit risks surrounding it that may lead to damage to banks, and may even lead to damage to the reputation and confidence of the banking system as a whole.The main role of supervisory control is to control credit by controlling it from excessive expansion during periods of economic inflation or its revitalization and improvement and expansion of credit transactions in cases of economic recession, or when central banks desire to support the national economy or support a sector of various economic sectors.The research has reached several important conclusions, including that the supervisory control carried out by central banks has an important role in protecting the banking system as a whole and preserving public and private money at the same time according to its laws, instructions and tools, and that central banks have their own tools through which they can control the volume of bank credit and control it. The lack of deep plans in activating bank credit at the same level as the plans that it has in achieving the maximum possible profit, by relying on another source of profits, which is the window for selling foreign currency and foreign transfers.